2022
DOI: 10.1590/1519-6984.256451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity of Dragon fruit based on ISSR markers in Colombia

Abstract: Selenicereus megalanthus H. is a tropical fruit belonging to the family Cactaceae, is rich in essential nutrients, antioxidants and bioactive components. It presents wide variability in different characteristics and a great demand in the market; however, genetic studies in Colombia are scarce. The main of this study was to characterize the genetic diversity of 76 yellow pitahaya genotypes with eight ISSR markers. Genetic parameters expected average heterozygosity (He), percentage of polymorphic loci, genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Morphological and molecular characterization studies carried out on the germplasm at the Department of Boyacá have shown that there is genetic diversity in the province of Lengupá, which is the basis for the establishment of any selection process that would identify elite materials that respond to the needs of the farmer, producers, and consumers. Selenicereus megalanthus, or yellow pitahaya, a native fruit tree, constitutes a key product for the fruit and vegetable sector, with significant demand for its flavor, appearance, quality, and nutraceutical properties (Morillo et al, 2021(Morillo et al, , 2022a. In addition, it has market potential, both domestically and internationally.…”
mentioning
confidence: 99%
“…Morphological and molecular characterization studies carried out on the germplasm at the Department of Boyacá have shown that there is genetic diversity in the province of Lengupá, which is the basis for the establishment of any selection process that would identify elite materials that respond to the needs of the farmer, producers, and consumers. Selenicereus megalanthus, or yellow pitahaya, a native fruit tree, constitutes a key product for the fruit and vegetable sector, with significant demand for its flavor, appearance, quality, and nutraceutical properties (Morillo et al, 2021(Morillo et al, , 2022a. In addition, it has market potential, both domestically and internationally.…”
mentioning
confidence: 99%
“…This fruit has attracted considerable attention from consumers because of the particular shape of the fruit and its richness in polyphenols, vitamins, sugar, amino acids, and betalains [20]. In addition, it presents great adaptation to extreme environmental conditions [12], mainly because of its broad phenotypic and genetic variations in its fruits and cladodes [3,6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Morillo et al [ 216 ] recently tested 76 H. megalanthus Columbian genotypes with eight ISSR markers and observed 225 alleles with 85–90 polymorphic loci. A heterozygosity rate of 0.34 and a genetic differentiation coefficient of 0.26 are attributed to high genetic diversity.…”
Section: Marker Technologymentioning
confidence: 99%